Is your article EV-TRACKed?. Issue 1 (1st December 2017) - Van Deun, Jan; Hendrix, An; ,
ABSTRACT: The EV-TRACK knowledgebase is developed to cope with the need for transparency and rigour to increase reproducibility and facilitate standardization of extracellular vesicle (EV) research. The knowledgebase includes a checklist for authors and editors intended to improve the transparency of methodological aspects of EV experiments, allows queries and meta-analysis of EV experiments and keeps track of the current state of the art. Widespread implementation by the EV research community is key to its success.